Monocyte and bone marrow macrophage transcriptional phenotypes in systemic juvenile idiopathic arthritis reveal TRIM8 as a mediator of IFN-γ hyper-responsiveness and risk for macrophage activation syndrome. Issue 5 (4th December 2020) - Schulert, Grant S; Pickering, Alex V; Do, Thuy; Dhakal, Sanjeev; Fall, Ndate; Schnell, Daniel; Medvedovic, Mario; Salomonis, Nathan; Thornton, Sherry; Grom, Alexei A
Abstract : Objectives: Systemic juvenile idiopathic arthritis (SJIA) confers high risk for macrophage activation syndrome (MAS), a life-threatening cytokine storm driven by interferon (IFN)-γ. SJIA monocytes display IFN-γ hyper-responsiveness, but the molecular basis of this remains unclear. The objective of this study is to identify circulating monocyte and bone marrow macrophage (BMM) polarisation phenotypes in SJIA including molecular features contributing to IFN response. Methods: Bulk RNA-seq was performed on peripheral blood monocytes (n=26 SJIA patients) and single cell (sc) RNA-seq was performed on BMM (n=1). Cultured macrophages were used to define consequences of tripartite motif containing 8 (TRIM8) knockdown on IFN-γ signalling. Results: Bulk RNA-seq of SJIA monocytes revealed marked transcriptional changes in patients with elevated ferritin levels. We identified substantial overlap with multiple polarisation states but little evidence of IFN-induced signature. Interestingly, among the most highly upregulated genes was TRIM8, a positive regulator of IFN-γ signalling. In contrast to PBMC from SJIA patients without MAS, scRNA-seq of BMM from a patient with SJIA and MAS identified distinct subpopulations of BMM with altered transcriptomes, including upregulated IFN-γ response pathways. These BMM also showed significantly increased expression of TRIM8. In vitro knockdown of TRIM8 in macrophages significantly reduced IFN-γ responsiveness. Conclusions: Macrophages with an 'IFN-γ response' phenotype and TRIM8 overexpression were expanded in the bone marrow from an MAS patient. TRIM8 is also upregulated in SJIA monocytes, and augments macrophage IFN-γ response in vitro, providing both a candidate molecular mechanism and potential therapeutic target for monocyte hyper-responsiveness to IFNγ in cytokine storms including MAS.